Measurement of the B ± production cross-section in pp collisions at √s = 7 TeV - Aaij, R; Beteta, C; Beteta, C; Adeva, B; Adinol, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; et al. (2012)
The production of B ± mesons in proton-proton collisions at √s = 7TeVis studied using 35 pb -1 of data collected by the LHCb detector. The B ± mesons are reconstructed exclusively in the B ± → J/ΨK ± mode, with J/Ψ→μ +μ -. The differential production cross-section is measured as a function of the B ± transverse momentum in the ducial region 0 < pT < 40 GeV=c and with rapidity 2:0 < y < 4:5. The total cross-section, summing up B + and B -, is measured to be σ(pp → B ±X; 0 < pT < 40 GeV=c; 2:0 < y < 4:5) = 41:4 ± 1:5 (stat:) ± 3:1 (syst:) μb. Copyright CERN.